DIGITAL TECHNOLOGY AND COSTUME DESIGN IN ANIMATTION: A STRUCTURALIST READING OF PETER DEL’S FROZEN - Akpan, Margaret; Udofia, Anietie Francis; Edem, Ndifreke Enefiok (International Review of Humanities Studies, 2020)
The deployment of digital technology to create captivating spectacles in films has reflected the boundlessness of man’s ingenuity in recreating his world. Such creativity reflects considerably in the fluidity of using the computer to generate human concepts of the role of costume grounded on theatrical system in animation. The world of animation is always synergized with marvels that defy the rational proofs for objectivity in the human world. This paper evaluates the use of digital technology to generate costume design to reflect the system of human thought in animation using Peter Del Velcho’s Frozen as paradigm. The paper uses qualitative research method to examine facts and bases its argument on Structuralism. Findings show that costume functions as a system in theatrical and film productions. In animation, the insight of human imagination through costume design is easily brought to bear, and the reality of creativity to man is ingrained in communication through captivating pictorials without impairment. Costume design can be generated from computer through knowledge and expertise. With the knowledge of computer, especially in the academic environment, unlimited streams of creativity may unfold to support the reality of entrepreneurial schemes in the society. When a costume is designed to conform to the order of a design system within a system of thought to pass on information, any medium can function as a dependable conduit to communicate.